Development of hepatic pathology in GBV‐B‐infected red‐bellied tamarins (Saguinus labiatus). Issue 12 (30th March 2020) - Dale, Jessica M.; Hood, Simon P.; Bowen, Ori; Bright, Helen; Cutler, Keith L.; Berry, Neil; Almond, Neil; Goldin, Robert; Karayiannis, Peter; Rose, Nicola J.
Abstract: GB virus B (GBV‐B) is a new world monkey‐associated flavivirus used to model acute hepatitis C virus (HCV) infection. Critical for evaluation of antiviral or vaccine approaches is an understanding of the effect of HCV on the liver at different stages of infection. In the absence of longitudinal human tissue samples at defined time points, we have characterized changes in tamarins. As early as 2 weeks post‐infection histological changes were noticeable, and these were established in all animals by 6 weeks. Despite high levels of liver‐associated viral RNA, there was reversal of hepatic damage on clearance of peripheral virus though fibrosis was demonstrated in four tamarins. Notably, viral RNA burden in the liver dropped to near undetectable or background levels in all animals which underwent a second viral challenge, highlighting the efficacy of the immune response in removing foci of replication in the liver. These data add to the knowledge of GBV‐B infection in New World primates which can offer attractive systems for the testing of prophylactic and therapeutic treatments and the evaluation of their utility in preventing or reversing liver pathology. Highlights: The development of liver pathology as a result of HCV infection is not straightforward to characterise. Serial biopsies from infected individuals are clinically impractical and unlikely to be available from early infection. We have characterised pathology in tamarins at various time‐points during infection with GBV‐B ‐ a surrogate model of HCV infection. We identified changes in the liver soon after infection; we also noted development of fibrosis which has not been reported previously in tamarins. This report highlights refinement of the tamarin model and its value in the pre‐clinical evaluation of antiviral treatments and vaccines.